Evaluation of the early outcomes of partial urogenital sinus mobilization in females with congenital adrenal hyperplasia - Ahmed Oshiba; Khaled Ashour; Ahmed Khairi; Sameh Shehata; Shaymaa ElSayed; Essam Elhalaby (SpringerOpen, 2020)
Abstract Background Congenital adrenal hyperplasia (CAH) is the most common cause of ambiguous genitalia with an incidence of 1 in 15,000 live births. Surgical reconstruction for girls with CAH and urogenital sinus (UGS) is a great challenge to create normal appearing and functional external genitalia. The purpose of this study is to evaluate the early outcomes of using partial urogenital sinus mobilization in feminizing genitoplasty in females with congenital adrenal hyperplasia regarding vaginal caliber, urinary continence, and genital appearance. Results Patient age at surgery ranged from 4 to 96 months (mean 19.4 months), with a mean follow-up of 15 months. Degree of virilization was Prader type III in 2 children (8%), type IV in 18 (72%), and type V in 5 (20%). Urogenital sinus length was 2.5 cm or less in 18 children. Cosmetic results were good in 19 patients (76%) and satisfactory in 6 (24%). Adequate caliber of the mobilized vagina was achieved in 24 patients (96%). Seven toilet trained children were assessed for bladder function. Only 1 patient was daytime incontinent and improved after few months with regular voiding. Urodynamics was done in toilet trained children and showed normal results. Conclusions The surgical procedure in general is consisting of clitoroplasty, labioplasty, urethroplasty, and vaginoplasty. Separation of the vagina from the urethra is a highly challenging surgical step and need good experience to perform. Partial urogenital sinus mobilization (PUM) has good results regarding the urinary continence, vaginal diameter, and cosmetic results in CAH patients.